2019
DOI: 10.33122/ijtmer.v1i2.14
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Problem Based Learning Model on Mathematical Learning Outcomes of 6th Grade Students of Elementary School Accredited B in Kendari City

Abstract: The purpose of this study was to determine the effect of problem-based learning models towards the mathematics learning outcomes of 6th-grade students of an Elementary School accredited B in Kendari City. This study is quantitative experimental research. The population in this were all 6th-grade students of an Elementary School accredited B in Kendari City. The technique of determining the sample was done by cluster random sampling. Data analysis used is descriptive statistics and inferential statistics where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 8 publications
3
17
0
7
Order By: Relevance
“…Problem Based Learning as a model gives freedom of thought and skill in solving problems to the students in the learning process by using a real problem (Sari, Wahyudi, & Hendrias, 2017). The results of the study conducted by Kaharuddin (2019) about the effect of the problem-based learning model on mathematic learning outcomes concluded that the application of a problem-based learning model has a positive effect on mathematics learning outcomes. Similar research was also conducted by Khoiriyah & Husamah (2018) about problem-based learning that creative thinking skills, problem-solving skills, and learning outcome of seventh-grade students with the conclusion that the application of PBL improves (1) the average of creative thinking skill was 11%, and the completion rate of 17.5%; (2) the average of problem-solving skills knowledge was 27% and the completion of 47%; and (3) the average score of learning outcomes was 3% and the completion rate was 15%.…”
Section: Introductionmentioning
confidence: 99%
“…Problem Based Learning as a model gives freedom of thought and skill in solving problems to the students in the learning process by using a real problem (Sari, Wahyudi, & Hendrias, 2017). The results of the study conducted by Kaharuddin (2019) about the effect of the problem-based learning model on mathematic learning outcomes concluded that the application of a problem-based learning model has a positive effect on mathematics learning outcomes. Similar research was also conducted by Khoiriyah & Husamah (2018) about problem-based learning that creative thinking skills, problem-solving skills, and learning outcome of seventh-grade students with the conclusion that the application of PBL improves (1) the average of creative thinking skill was 11%, and the completion rate of 17.5%; (2) the average of problem-solving skills knowledge was 27% and the completion of 47%; and (3) the average score of learning outcomes was 3% and the completion rate was 15%.…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of the problem-based learning model in elementary schools has also been done before. Like research by Kaharuddin (2019) and Kartikasari & Widjajanti (2017). Both studies were conducted with research subjects coming from high school elementary school students.…”
Section: |mentioning
confidence: 55%
“…In the investigation step, students are asked to look for data on the problem and find out the correct calculation process if the problems encountered can be calculated in value. Through this stage of the investigation, students' process skills can be honed primarily in their ability to process numeracy and other mathematical operations (Risdianti, 2017;Kaharuddin, 2018). The mathematical operations ability in this study relates to applying and integrating mathematical operations to solve problems in everyday life.…”
Section: Aspect Of Calculation Process Abilitymentioning
confidence: 97%
“…Through those stage of investigation, students' process abilities can be honed, primarily in their ability to calculating process and other mathematical operations (Risdianti, 2017). Through problem-based student's worksheet, students are taught to be able to connect everyday problems with mathematical concepts, get used to answering mathematical questions with mathematical communication, solve problems using mathematical formulas or concepts, and relating the daily problems with appropriate theory (Kaharuddin, 2018).…”
Section: Aspect Of Calculation Process Abilitymentioning
confidence: 99%